Fear of Falling and Its Relationship with Quality of Life in the Elderly Attending a Family Medicine Clinic in South-South Nigeria - S. S. Uriah; Oguzor Ununuma Chimiyuma; C. T. Atata; N. M. Nwanze; P. O. Dienye (Nigerian Journal of Medicine)
Introduction: Increased morbidity, reduced activity, and a greater prevalence of fear of falling (FOF) are all associated with aging. The elderly’s quality of life (QOL) may as a result be harmed by these aforementioned reasons. Research examining FOF and its impact on elderly people’s QOL from Africa are uncommon. FOF is a loss of confidence in one’s balance abilities which affects most elderly at some point in their lives with a significant impact on their QOL. This research examined the association between FOF and its relationship with QOL among the elderly visiting a tertiary hospital in Port Harcourt, Rivers State. Methodology: In this cross-sectional research conducted at a healthcare facility, 292 participants were selected using a systematic selection procedure. Data were gathered by the administration of a questionnaire by trained interviewers. The questionnaire included two tools namely the Modified Fall Efficacy scale to assess the FOF in the respondents and the 12-item short health survey form (SF-12) to access the QOL of recruited participants. The questionnaire also included the age and gender of the participants. We used Microsoft Excel to code the survey responses, and then we exported them to SPSS 26.0. In order to determine the association between FOF and QOL, the data was analysed using descriptive statistics, proportions, frequencies and an independent t-test to compare the mean scores of the age of the respondents and the domains of QOL (physical component score [PCS-12] and mental component score [MCS-12]). Pearson correlation was also used. Results: The average age of the responders was 68.5 years ± 6.6 years. More of those who took part were females and they were more likely than men to be highly scared of falling (37.7% vs. 11.3%, respectively). The FOF was most prevalent among women aged 60–69 (36.3%). Respondents’ very low PCS-12 scores indicated a degree of physical dysfunction, which was associated with FOF. Since the scores were similar in both the group with a FOF (Modified Fall Efficacy scale [MFES] <8) and the group without a FOF (MFES > 8), there was no correlation between MCS and FOF. Conclusion: As a result of the study’s findings, an association between FOF and physical function – and the lack or presence of disease, the authors recommend frequently investigating this anxiety. Healthcare providers providing geriatric care should prioritise implementing targeted methods to reduce falls and increase physical activity among the elderly to enhance their QOL and reduce the risk of falls, according to QOL domain scores.